Soil physical and microbiological attributes cultivated with the common bean under two management systems - Gennaro, Lorena Adriana de; Souza, Zigomar Menezes de; Marinho Weill, Mara de Andrade; Souza, Gustavo Soares de; Alves, Marlene Cristina [UNESP] (Univ Federal Ceara, Dept Geol, 2014)
Agricultural management systems can alter the physical and biological soil quality, interfering with crop development. The objective of this study was to evaluate the physical and microbiological attributes of a Red Latosol, and its relationship to the biometric parameters of the common bean (Phaseolus vulgaris), irrigated and grown under two management systems (conventional tillage and direct seeding), in Campinas in the state of Sao Paulo, Brazil. The experimental design was of randomised blocks, with a split-plot arrangement for the management system and soil depth, analysed during the 2006/7 and 2007/8 harvest seasons, with 4 replications. The soil physical and microbiological attributes were evaluated at depths of 0.00-0.05, 0.05-0.10, 0.10-0.20 and 0.20-0.40 m. The following were determined for the crop: density, number of pods per plant, number of beans per pod, thousand seed weight, total weight of the shoots and harvest index. Direct seeding resulted in a lower soil physical quality at a depth of 0.00-0.05 m compared to conventional tillage, while the opposite occurred at a depth of 0.05-0.10 m. The direct seeding showed higher soil biological quality, mainly indicated by the microbial biomass nitrogen, basal respiration and metabolic quotient. The biometric parameters in the bean were higher under the direct seeding compared to conventional tillage.

Os sistemas de manejo agrícola do solo podem alterar sua qualidade física e biológica, interferindo no desenvolvimento das culturas. O objetivo do trabalho foi avaliar os atributos físicos e microbiológicos de um Latossolo Vermelho e sua relação com parâmetros biométricos do feijoeiro (Phaseolus vulgaris) irrigado cultivado em dois sistemas de manejo (preparo convencional e semeadura direta), em Campinas-SP. O delineamento experimental foi em blocos casualizados com arranjo em parcelas subdivididas para sistema de manejo e profundidade do solo, analisados nas safras de 2006/07 e 2007/08, com 4 repetições. Os atributos físicos e microbiológicos do solo foram avaliados nas profundidades de 0,00-0,05; 0,05-0,10; 0,10-0,20 e 0,20-0,40 m. Para a cultura foram determinados: estande, número de vagens por planta, número de grãos por vagem, massa de mil grãos, massa da parte aérea total e o índice de colheita. A semeadura direta resultou em menor qualidade física do solo na profundidade de 0,00-0,05 m em relação ao preparo convencional, ocorrendo o inverso na profundidade de 0,05-0,10 m. O solo em que foi feita a semeadura direta apresentou melhor qualidade biológica, indicada, principalmente, pelo nitrogênio da biomassa microbiana, respiração basal e quociente metabólico. Os parâmetros biométricos do feijoeiro foram superiores no sistema semeadura direta em relação ao convencional.
Keywords: Soil structure; Soil organic matter; Soil microbial activity; Direct seeding; Phaseolus vulgaris.; Estrutura do solo; Matéria orgânica do solo; Atividade microbiana do solo; Semeadura direta; Phaseolus vulgaris